Analysis Of Solar Panel Efficiency In Solar Power Generation Systems As A Learning Media For Renewable Energy In Tropical Areas - Puspitasari, Pipit (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Renewable energy, particularly solar energy, plays a crucial role in addressing the limitations of fossil fuels and environmental sustainability issues, especially in tropical regions such as Indonesia. In addition to serving as an alternative energy source, Solar Power Generation Systems (SPGS/PLTS) also have potential as contextual learning media in vocational education. This study aims to analyze the efficiency of solar panels in a solar power generation system and examine their utilization as learning media for renewable energy education among students of the Renewable Energy Engineering Program at Akademi Komunitas Olat Maras (AKOM). This research employed a quantitative approach using descriptive methods and simple experiments. The research object was the solar power generation system and solar panels, while the research subjects were students involved in the learning activities. Data were collected through measurements of solar irradiance, input and output power, learning observations, and simple questionnaires. The results indicate that the solar panels achieved an operationally feasible efficiency level under tropical conditions. Furthermore, the use of the solar power system as a learning medium increased student engagement and improved their understanding of renewable energy concepts. This study concludes that solar power systems are effective as contextual and practical learning media in vocational education and have positive implications for the development of renewable energy learning and curriculum.